JENIS, STATUS DAN PEMANFAATAN TUMBUHAN JENIS POHON DI DESA ADAT BATURNING, KECAMATAN ABIANSEMAL, KABUPATEN BADUNG, BALI - Adriani Astiti, N. P.; Kawuri, Retno; Ginantra, I K. (Bumi Lestari; Vol 8 No 2 (2008))
There were 65 species of trees have been identified in Baturning village, District of Abiansemal, Regency of Badung, Bali, which were spread out around the river bank, cemetery (around Dalem temple), around the settlement, non-irrigated farm (plantation or “tegalan”) and rice field. Thirty eight (38) % out of them were observed to be available around the settlement. Most of trees in Baturning (61 species or 94%) have been used by the local community. The rest were uncultivated. From the use, trees in Baturning most were used for human consumption (24%). On the village has not been found protected species, even though in the village were found 22 species of trees which considered to be rare in Bali, namely: Bayur, Bentenung, Beringin, Cempaka, Ee, Jaka, Jeruk Bali, Juwet, Kelor, Kendal, Klampuak, Lempeni, Lenggung, Mahoni, Mengkudu, Palem Raja, Poh-Pohan, Pule, Sandat, Sentul, Udu, and Wani.
Keywords: plants, status, usage, protected, Baturning, Bali